2017
DOI: 10.1002/pen.24624
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous polyacrylamide hydrogels with tailored porosity and mechanical properties via microphase separation in the presence of hydroxyethylcellulose

Abstract: In this work hydroxyethylcellulose (HEC) was employed to prepare macroporous polyacrylamide (PAAm) hydrogels with different porosities and degrees of interconnectivity. The porosity and the equilibrium mass swelling ratio of hydrogels equilibrated in 0.1 M NaCl increased with the amount of HEC employed in the reaction mixture. Tensile and fracture tests were performed to investigate the mechanical behavior of both as prepared hydrogels and of hydrogels equilibrated in 0.1 M NaCl. As prepared hydrogels displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
2
2
0
Order By: Relevance
“…For instance, Yoshinobu et al (1992) found that increasing the cross-linker content in cellulosic hydrogels decreased the porosity percentage, similar to our findings. Bignotti et al (2017) also observed that an increase in Natrosol content increased the porosity of HEC and polyacrylamide-based hydrogels, supporting our results. Likewise, Bashir et al (2020) reported that increasing the amount of Pectin and Acrylic Acid in HPMC-Pectin-Acrylic Acid co-polymerized hydrogels increased the porosity proportionally, consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Yoshinobu et al (1992) found that increasing the cross-linker content in cellulosic hydrogels decreased the porosity percentage, similar to our findings. Bignotti et al (2017) also observed that an increase in Natrosol content increased the porosity of HEC and polyacrylamide-based hydrogels, supporting our results. Likewise, Bashir et al (2020) reported that increasing the amount of Pectin and Acrylic Acid in HPMC-Pectin-Acrylic Acid co-polymerized hydrogels increased the porosity proportionally, consistent with our observations.…”
Section: Discussionsupporting
confidence: 90%
“…Figure 3B showed the increase in porosity (71.87%–84.34%) of the hydrogel with an increasing mass fraction of PPG. In general, the mechanical stiffness decreased regularly as the porosity was increased 29,30 . The hydrogels we prepared also conform to this law.…”
Section: Resultssupporting
confidence: 67%
“…In general, the mechanical stiffness decreased regularly as the porosity was increased. 29,30 The hydrogels we prepared also conform to this law. The compressive strength of the solid-state hydrogel gradually decreased from 3.88 to 0.44 MPa.…”
Section: Resultsmentioning
confidence: 78%
“…An addition of a hydrophilic agent into the reaction mixture during polymerization is another way how to prepare microporous hydrogels. For example, Bignotti et al [43] used hydroxyethylcellulose for this purpose and prepared PAAm hydrogels with the porosity ranging from 24% to 45%.…”
Section: Introductionmentioning
confidence: 99%